Therapeutic resistance and combination therapy for cancer: recent developments and future directions - Chendil Damodaran; Je-Yoel Cho; Cenap Güngör (Scientific Reports)
Abstract The diverse and heterogeneous nature of cancer is a fundamental characteristic that is responsible for therapy resistance, progression, and recurrence of disease. In order to enhance therapeutic efficacy, novel combination therapies are currently being proposed and utilized in clinical practice to effectively manage or retard disease progression. Several factors contribute to therapeutic resistance, including elevated expression of survival factors, mutations in genes that limit therapeutic effectiveness, multidrug resistance, and the potential involvement of cancer stem cells. This Scientific Reports Collection covers the underlying mechanisms responsible for therapeutic resistance. Additionally, the publications from this Collection highlight numerous innovative molecules to overcome this resistance and significantly sensitize tumors across various cancer models.